2003
DOI: 10.1152/japplphysiol.00132.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in ethanol sensitivity in two tests of motor incoordination

Abstract: Motor incoordination is frequently used as a behavioral index of intoxication by drugs that depress the central nervous system. Two tasks that have been used to assay incoordination in mice, the balance beam and the grid test, were evaluated to optimize aspects of apparatus and testing procedures for studying genetic differences. Mice of eight inbred strains were given one of several doses of ethanol or saline and tested for intoxication. Strains differed in sensitivity to ethanol in both tests, indicating a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 38 publications
2
82
0
Order By: Relevance
“…Association analysis revealed that a number of genes encoding proteins in the NMDA/glutamate signaling pathway are involved in the ability to traverse a wire grid; however, the particular genes involved are dependent on whether or not the subjects are under the influence of ethanol (Crabbe et al, 2003). NOS, Grin1, and Grin2C mRNA levels are correlated positively with distance traveled by salinetreated animals.…”
Section: Region-enriched Genesmentioning
confidence: 99%
“…Association analysis revealed that a number of genes encoding proteins in the NMDA/glutamate signaling pathway are involved in the ability to traverse a wire grid; however, the particular genes involved are dependent on whether or not the subjects are under the influence of ethanol (Crabbe et al, 2003). NOS, Grin1, and Grin2C mRNA levels are correlated positively with distance traveled by salinetreated animals.…”
Section: Region-enriched Genesmentioning
confidence: 99%
“…Experiments were performed as described by Crabbe et al (2003a). Briefly, mice were given four training trials on a balance beam (width, 19 mm; length, 90 cm).…”
Section: Ataxia Testingmentioning
confidence: 99%
“…On the test day, animals received an intraperitoneal injection of 20% Et-OH (2 g/kg) or an equal volume of physiological saline. Behavioral tests were performed 10 min after the injection to allow ethanol concentration to reach the maximum level in the brain (Crabbe et al 2003).…”
Section: Behavioral Testsmentioning
confidence: 99%